2016
DOI: 10.1002/acp.3253
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Enhanced Cognitive Interview With a New Interview Strategy: Category Clustering Recall

Abstract: Increasing recall is crucial for investigative interviews. The Enhanced Cognitive Interview (ECI) has been widely used for this purpose and found to be generally effective. We focused on further increasing recall with a new interview strategy, Category Clustering Recall (CCR). Participants watched a mock robbery video and were interviewed 48 hours later with either the: (1) ECI; (2) Revised Enhanced Cognitive Interview 1 (RECI1)-with CCR instead of the change order mnemonic during the second recall; or (3) Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(88 citation statements)
references
References 47 publications
(85 reference statements)
4
84
0
Order By: Relevance
“…Third, witness-generated segmentation of an event into its component parts is consistent with witness-compatible questioning (e.g., MacDonald, Snook, & Milne, 2017) in that it provides scaffolding for the individual processing styles of autistic (and indeed TD) witnesses (e.g., Pellicano & Burr, 2012) and allows the interviewee to revisit topics in the order that they have first recalled them. Paulo, Albuquerque, and Bull (2016) and Paulo, Albuquerque, Vitorino, and Bull (2017) recently developed an additional component of the CI whereby witnesses are explicitly instructed to organise their episodic recall semantically rather than temporally, on the basis that recalling a crime event in category clusters may be more compatible with an individual witness' mental organisation of the event. Following free recall, witnesses are then instructed to recall everything they can remember, focusing on just one category of information at a time (e.g., objects, locations, people, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, witness-generated segmentation of an event into its component parts is consistent with witness-compatible questioning (e.g., MacDonald, Snook, & Milne, 2017) in that it provides scaffolding for the individual processing styles of autistic (and indeed TD) witnesses (e.g., Pellicano & Burr, 2012) and allows the interviewee to revisit topics in the order that they have first recalled them. Paulo, Albuquerque, and Bull (2016) and Paulo, Albuquerque, Vitorino, and Bull (2017) recently developed an additional component of the CI whereby witnesses are explicitly instructed to organise their episodic recall semantically rather than temporally, on the basis that recalling a crime event in category clusters may be more compatible with an individual witness' mental organisation of the event. Following free recall, witnesses are then instructed to recall everything they can remember, focusing on just one category of information at a time (e.g., objects, locations, people, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Following free recall, witnesses are then instructed to recall everything they can remember, focusing on just one category of information at a time (e.g., objects, locations, people, etc.) Whilst category clustering recall has been shown to elicit more correct details from TD witnesses (e.g., Paulo et al, 2016Paulo et al, , 2017Thorley, 2018) the interviewer directs the nature and order of categories to be recalled and it is preceded by unbound free recall, which is problematic for autistic witnesses. The WAFA interview, in contrast, utilises a similar principle of category clustering but these categories are events rather than types of details and are determined by the witness rather than the interviewer at the outset.…”
Section: Discussionmentioning
confidence: 99%
“…This recall strategy consisted on asking participants to recall one more time everything they could remember about the crime episode but this time organize their recall/speech into seven information categories (person details; person location details; object details, object location details; action details, conversation details; sound details). Paulo et al (2016) suggested using these information categories because (i) these are frequently important topics for a police investigation, therefore commonly used in investigative interviews' coding process; (ii) these are very broad categories which are present in almost every crime, therefore minimizing the interviewer's impact on the participant's report and replacing the use of specific questions;…”
Section: Methodsmentioning
confidence: 99%
“…This recall strategy consists of asking witnesses to recall one more time everything they can remember about the crime episode but, this time, witnesses are asked to organize their recall/speech into broad information categories which are present in almost every crime (i.e., person details, object details, location details, action details, conversation details and sound details), instead of temporal clusters as used with the change order mnemonic. Paulo et al (2016) found participants who used CCR during a second recall attempt were able to recall substantially more information without compromising accuracy in comparison with participants who used the change order mnemonic, also during a second recall attempt. Furthermore, they believe this interview strategy may have several advantages: (i) Recalling a crime event in category clusters might be more natural and compatible with the witness' mental organization of the event because people often naturally/spontaneously encode, organize and recall information in semantic categories (Dalrymple-Alford & Aamiry, 1969;Manning & Kahana, 2012;Robinson, 1966).…”
mentioning
confidence: 87%
See 1 more Smart Citation